2021
DOI: 10.1093/ons/opab021
|View full text |Cite
|
Sign up to set email alerts
|

The Retroauricular Incision as an Effective and Safe Alternative Incision for Decompressive Hemicraniectomy

Abstract: BACKGROUND The reverse question mark (RQM) incision has been traditionally utilized to perform decompressive hemicraniectomies (DHC) to relieve refractory intracranial hypertension. Alternative incisions have been proposed in the literature but have not been compared directly. OBJECTIVE To present the retroauricular (RA) incision as an alternative incision that we hypothesize will increase calvarium exposure to maximize the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…The findings of Veldeman et al in a large retrospective study including 186 patients showed statistically significant fewer surgical site infections after cranioplasty, following DHC done with RMF incision as opposed to DHC performed with the "Dandy flap" incision (6.3% vs. 14%) [ 6 ]. In accordance with our results, Dowlati et al detected in a recent study a lower rate of wound complications with the RMF incision compared to DHC performed with the "Dandy flap" incision (8.3% vs. 14%) in a larger sample of 106 patients also without reaching statistically significant difference [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
“…The findings of Veldeman et al in a large retrospective study including 186 patients showed statistically significant fewer surgical site infections after cranioplasty, following DHC done with RMF incision as opposed to DHC performed with the "Dandy flap" incision (6.3% vs. 14%) [ 6 ]. In accordance with our results, Dowlati et al detected in a recent study a lower rate of wound complications with the RMF incision compared to DHC performed with the "Dandy flap" incision (8.3% vs. 14%) in a larger sample of 106 patients also without reaching statistically significant difference [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
“…We have read with great interest the results published by Dowlati et al 1 in regard to the retroauricular ending incision as an alternative to the reversed question mark incision for decompressive hemicraniectomy. In a comparative retrospective series, the authors compared 63 patients via the traditional reversed question mark incision with 43 cases operated via a retroauricular ending alternative incision type.…”
mentioning
confidence: 99%
“…The 2014 scientific statement released by the American Heart Association and American Stroke Association ( 2 ) suggested that a bone flap of ≥12 cm is performed in DC. In an attempt to further optimise the procedure, numerous other studies have been conducted including the investigation of different bone flap sizes ( 18 24 ), retroauricular surgical incision ( 25 ), resection of the temporalis muscle ( 26 ), temporal lobectomy ( 20 , 21 , 27 – 29 ), and various forms of duroplasty ( 30 , 31 ). These adjunctive manoeuvres, although effective, have significant disadvantages such as the risk of intraoperative or postoperative haemorrhage in lobectomies ( 20 , 21 , 27 – 29 ) and cosmetic and masticatory defects for temporalis resection ( 26 ).…”
Section: Introductionmentioning
confidence: 99%